Recent regional developments in red tape reduction - a content analysis of Web of Science journals - Kovač, Polonca (Lex localis, 2017)
The economic crisis has led to slowdowns in both national and wider regional economies. A comparatively successful approach to mitigate its impacts is red tape or administrative burden reduction through procedural and other simplifications. This paper explores the relevant public policies examined in 70 scientific articles, classified in the Web of Science under 'red tape' or 'administrative burden' and related terms and published between 2013 and 2015. The study focuses on the understanding of red tape in terms of regional relevance, dominant doctrinal and disciplinary framework and types of cooperation in research, in an attempt to identify inter-boundaries dialogue as a means of cross-regional learning. The research findings show a prevailing field role of economic, managerial and procedural measures since red tape reduction is most often considered within organizational performance and the neo-liberalistic doctrines. Moreover, cooperation between regions is low, the geographic focus is rather limited, and there is little evidence of collaboration between scholars and practitioners as well as a low practical applicability of research. This means that more holistic policies to withstand economic slowdowns and pursue sustainable societal development are less effective than they would be if they were grounded in inter-regional cooperation and good governance interdisciplinarity.
Keywords: administrativne ovire; birokracija; dobra uprava; javna uprava